Stabilizing the Fe Species of Nickel-Iron Double Hydroxide via Chelating Asymmetric Aldehyde-Containing THB Ligand for Long-Lasting Water Oxidation - Huang, Yifan (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2024 Wiley‐VCH GmbH.